A dialogue between a philosopher and a student, of the common laws of England - Hobbes, Thomas, 1588-1679 (Hobbes, Thomas, 1588-1679. Works. 1983 ;, 2005)
As a critique of common law by a great philosopher, this text should be of interest to anyone studying English political thought or legal theory.